Representation of Collective Past in German and Russian Media[ - L. N. Rebrina; N. L. Shamne (Научный диалог, 2017)
The results of the comparative analysis of the patterns of representation of collective memory in forming the image of the past in German and Russian media are presented. Collective memory is interpreted by the authors in the framework of the theory of social communication as a discursive construct, functioning in the social chronotopos as the set of actions of a society for symbolic reconstruction of the past in the present. The described semantic interaction is characterized by the subject-object relations between the sender and the receiver of the message, manipulative nature, “packaging” of meaning in the content before a communicative act, impact on cognitive and axiological sphere of the addressee. On the Russian and German-language material the argumentation and compositional tactics of implementation of the strategies for positive and negative representations of the past and the tactics of deactualization of fragments of the past in the media are analyzed. General and national-specific features of reactualization and reinterpretation of collective memory in two linguistic cultures are defined. The authors come to the conclusion that the overall discursive practices in Russian media are distinguished by the desire of the sender to the emotional involvement of the recipient, an active appeal to the individual experience of the sender, the high relevance of the identification and orientation on the implied opposite position of the message recipient.